2014
DOI: 10.2172/1339441
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress on U.S. Power Production at Decadal Time Horizons

Abstract: Engineering provided software such as ArcGIS and the required computational resources. Janet Yun, an undergraduate student in Civil and Environmental Engineering at Northeastern University, helped during the initial analysis phase through an independent study program. We are grateful to Tyler Hall, a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Key infrastructure allowing society to function, including power plants and transportation systems, are built to sustain specific levels of climate extremes and perform optimally in it's expected climate. Studies have shown that the changing climate has had, and will continue to have, significant impacts on critical infrastructure [13,31]. Furthermore, climate change is having dramatic negative effects to ecosystems, from aquatic species to forests ecosystems, caused by increases in greenhouse gases and temperatures [43,32,20].…”
Section: Introductionmentioning
confidence: 99%
“…Key infrastructure allowing society to function, including power plants and transportation systems, are built to sustain specific levels of climate extremes and perform optimally in it's expected climate. Studies have shown that the changing climate has had, and will continue to have, significant impacts on critical infrastructure [13,31]. Furthermore, climate change is having dramatic negative effects to ecosystems, from aquatic species to forests ecosystems, caused by increases in greenhouse gases and temperatures [43,32,20].…”
Section: Introductionmentioning
confidence: 99%
“…Key infrastructure allowing society to function, including power plants and transportation systems, are built to sustain specific levels of climate extremes and perform optimally in it's expected climate. Studies have shown that the changing climate has had, and will continue to have, significant impacts on critical infrastructure [35,87]. Furthermore, climate change is having dramatic negative effects to ecosystems, from aquatic species to forests ecosystems, caused by increases in greenhouse gases and temperatures [118,88,44].…”
Section: Introductionmentioning
confidence: 99%